2007
DOI: 10.1590/s0004-28032007000200003
|View full text |Cite
|
Sign up to set email alerts
|

Perfil socioeconômico e nutricional de pacientes com doença inflamatória intestinal internados em um hospital universitário

Abstract: RESUMO -Racional -Doenças inflamatórias intestinais incluem distúrbios inflamatórios crônicos e recidivantes, representados pela retocolite ulcerativa e doença de Crohn, comumente associadas à desnutrição. Objetivo -Caracterizar o perfil nutricional e socioeconômico dos pacientes internados no Hospital das Clínicas de Pernambuco, Recife, PE. Métodos -Estudo do tipo transversal realizado na clínica de gastroenterologia, previamente aprovado pela comissão de ética para estudos em humanos. Os métodos incluíram da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
1
6
0
12
Order By: Relevance
“…In our population, there is little research on the presence of these alterations in this group of patients. 8 Our study found a higher female prevalence for both IBDs, as observed in other Brazilian studies, 4-6 namely 57.9% women with CD and 77.7% with UC. In agreement with the literature, 7 a higher incidence of IBD was found among young adults, with medians of 39.5 and 39 years for CD and UC, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…In our population, there is little research on the presence of these alterations in this group of patients. 8 Our study found a higher female prevalence for both IBDs, as observed in other Brazilian studies, 4-6 namely 57.9% women with CD and 77.7% with UC. In agreement with the literature, 7 a higher incidence of IBD was found among young adults, with medians of 39.5 and 39 years for CD and UC, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Undernutrition is a major complication among these patients and it is strongly associated with worst prognostic and increased risk of clinical and surgical complications (26) . Its prevalence may vary from 23% in outpatient units to 85% in hospitalized subjects (8,29) . Factors associated with undernutrition in these patients are inadequate food intake, chronic inflammatory state with increased energy requirements and losses from the gastrointestinal tract (8,26) .…”
Section: Introductionmentioning
confidence: 99%
“…Prevalece, ainda, em moradores de áreas urbanas, pessoas de classes econômicas mais altas, fumantes e parentes de primeiro grau de indivíduos acometidos. 14 Dados epidemiológicos e mórbidos dos pacientes portadores destas doenças, no estado de Mato Grosso, não foram encontrados em levantamento bibliográfico realizado de forma ampla e recente. Julgamos que o conhecimento destas informações pode contribuir de forma satisfatória para a assistência prestada a estes pacientes.…”
Section: Introductionunclassified